Violência obstétrica em (des)foco: uma avaliação da atuação do Judiciário sob a ótica do TJMA, STF e STJ - SERRA, Maiane Cibele de Mesquita (2018)
Obstetric violence is a form of gender violence and institutional violence imbricated by power relations being characterized by the appropriation of the body and the reproductive processes of the parturient woman by the health professionals, through a dehumanized treatment, abuse of medicalization and pathologization of natural processes. This type of violence constitutes a violation of fundamental rights, human rights and also constitutional rights and bioethical principles, since it imposes the loss of autonomy and the loss of women to freely decide about their own body and sexuality, culminating in negative consequences and disastrous outcomes for the quality of life of these women. The present study aimed to evaluate, considering the judgments of the Court of Justice of Maranhão (TJMA), the Superior Court of Justice (STJ) and the Supreme Federal Court (STF), between the years of 2010 and 2016, the argumentative perspectives of the Judiciary in cases of obstetric violence, debating about it´s performance. Several complementary methodological procedures were used to carry out the research, such as, bibliographic research, documentary analysis of the judgments, semi-structured interviews with key informants (TJMA civil appellate judges), and systematic observation registered in the field diary during all the visits that took place in the TJMA. Judgments and semistructured interviews were analyzed through the technique of content analysis proposed by Laurence Bardin (1977) in order to understand the explicit or implicit meanings contained in the judgments and speeches of the agents interviewed. In a conclusive way, in order to reach the proposed objective, the convergences and divergences observed in the judgments, interviews and systematic observation with records in the field diary were presented, highlightening all the data collected to complete the present study.